2016
DOI: 10.1371/journal.pone.0160779
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Receptor 1 Dampens the Development of Allergic Eosinophilic Airway Inflammation

Abstract: The function of NCR1 was studied in a model of experimental asthma, classified as a type 1 hypersensitivity reaction, in mice. IgE levels were significantly increased in the serum of OVA immunized NCR1 deficient (NCR1gfp/gfp) mice in comparison to OVA immunized wild type (NCR1+/+) and adjuvant immunized mice. Histological analysis of OVA immunized NCR1gfp/gfp mice revealed no preservation of the lung structure and overwhelming peribronchial and perivascular granulocytes together with mononuclear cells infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Meanwhile, increased production of IgE in serum of mice exposed to S. aureus or the combination of PM and S. aureus correlated positively with the upregulated Th2 cytokine production. Several studies reported that the development of allergic airway inflammation and bronchial asthma was associated with elevated IgE levels, the predominance of Th2 cytokine production, and eosinophils related-inflammation of the airways [7, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, increased production of IgE in serum of mice exposed to S. aureus or the combination of PM and S. aureus correlated positively with the upregulated Th2 cytokine production. Several studies reported that the development of allergic airway inflammation and bronchial asthma was associated with elevated IgE levels, the predominance of Th2 cytokine production, and eosinophils related-inflammation of the airways [7, 26].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that NKp46 signaling enhances allergic responses. In contrast, a separate study using a delayed type I hypersensitivity model, showed that NKp46 signaling suppressed the development of airway eosinophilia following intranasal OVA challenge (179). It will be interesting to see which NKp46-expressing cell types, such as NK cells, ILC1 or ILC3, might be responsible for either suppressing (179) or augmenting (178) airway inflammation in models of type I and type IV hypersensitivity, respectively.…”
Section: Ncrs and Their Ligands In Allergymentioning
confidence: 99%
“…It should be noted, however, that also transgenic mice exist which specifically react to more relevant allergens, like the 1-DER mice expressing the T-cell receptor specific for the major house dust mite allergen Der p 1 from Dermatophagoides pteronyssinus [ 16 ]. Recent reports, all using ovalbumin have shown aggravation of asthma by pentraxin 3 [ 17 ], prostaglandin E2 [ 18 ], IL-15-deficiency [ 19 ] or suppression of asthma by anti-inflammatory protein 2 from hookworms [ 20 ▪▪ ], natural killer (NK) receptor 1 [ 21 ] and inhibition of hypoxia inducible factor-1α [ 22 ]. Sensitization with ovalbumin was usually performed by the intraperitoneal route, which, though valid, hardly represents the natural respiratory sensitization process in humans or animals.…”
Section: Introductionmentioning
confidence: 99%